Here tomorrow. - Marcoci, Roxana; Pintaric, Snjezana (Zagreb : Muzej Suvremene Umjetnosti, 2002)
Bitanga, Iva-Matija ; Blace, Zeljko ; Bura, Ivan ; Crtalic, Marijan ; Faktor, Ivan ; Fijolic, Ivan ; Floricic, Alen ; Franke, Ivana ; Frelih, Vladimir ; Friscic, Danko ; Gotovac, Tomislav ; Grubic, Igor ; Hewitt, Nicole ; Ilic, Aleksandar Battista ; Ivekovic, Sanja ; Keser, Ivana ; Kopljar, Zlatko ; Kozaric, Ivan ; Kuluncic, Andreja ; Labin Art Press ; Leko, Kristina ; Maljkovic, David ; Martinis, Dalibor ; Marusic-Klif, Ivan ; Mezak, Davor ; Oki, Dan ; Opalic, Ana ; Petercol, Goran ; Platforma 9,81 ; Poljak, Renata ; Rogic, Frane ; Savic-Gecan, Tomo ; Seric, Ana ; Skofic, Goran ; Sterle, Sandra ; Stilinovic, Mladen ; Tolj, Slaven ; Vujicic, Silvio ; Vukelic, Leo
biog. p.170-215
Here Tomorrow, Muzej Suvremene Umjetnosti, Zagreb (Museum of Contemporary Art), 4.10. - 3.11.2002
Kroatisch & Engels
kunstcatalogus
Keywords: Kroatië